Kontestasi pendidikan keislaman dan pendidikan umum: persepsi masyarakat tentang sumber kekuatan mobilitas sosial di kabupaten bone - Nursyirwan Nursyirwan (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This study examines community perceptions about the ability of Islamic educational institutions and graduate competencies in driving social change vertically in Bone Regency, South Sulawesi. Islamic education is considered powerless in encouraging progress and giving graduates a future. This descriptive qualitative study found a different fact where the misperception about the ability of Islamic education was widespread. Observations and interviews show that religious education institutions have been actively involved in providing policy perspectives in the regions and Islamic education graduates have proven to play an active role not only in the religious field but also in various fields of community and government life. The ability of graduates of Islamic educational institutions even outperformed graduates of non-religious educational institutions because religious graduates have competence in the religious and general fields as well. The results of this study suggest the need for popularization of Islamic educational institutions in the community and intensification of communication with the community so that the existence and progress of Islamic education institutions can be represented according to their position and role in society.Penelitian ini mengkaji persepsi masyarakat tentang kemampuan lembaga pendidikan keislaman dan kompetensi lulusan dalam mendorong perubahan sosial secara vertikal di Kabupaten Bone, Sulawesi Selatan. Pendidikan keislaman dianggap tidak berdaya dalam mendorong kemajuan dan memberi masa depan pada lulusan. Penelitian yang bersifat kualitatif deskriptif ini menemukan fakta yang berbeda di mana mispersepsi tentang kemampuan pendidikan keislaman terjadi secara meluas. Hasil pengamatan dan wawancara memperlihatkan bahwa lembaga pendidikan keagamaan telah terlibat secara aktif dalam memberikan perspektif kebijakan di daerah dan lulusan pendidikan keislaman terbukti berperan aktif tidak hanya dalam bidang keagamaan tetapi juga dalam berbagai bidang kehidupan masyarakat dan pemerintahan. Kemampuan lulusan lembaga pendidikan keislaman bahkan mengungguli lulusan lembaga pendidikan non-keagamaan karena lulusan keagamaan memiliki kompetensi dalam bidang keagamaan dan umum sekaligus. Hasil penelitian ini menyarankan perlunya popularisasi lembaga pendidikan keislaman di dalam masyarakat dan intensifikasi komunikasi dengan masyarakat agar keberadaan dan kiprah lembaga pendidikan keislaman dapat direpresentasikan sesuai dengan posisi dan peran dalam masyarakat.